Corporate Financial Reporting in Austria : An Overview - Lindner, Bernhard (World Bank, Vienna, 2016)
The purpose of this report on corporate financial reporting in Austria is to describe the key features of Austria’s corporate financial reporting environment as well as its practical application in regard to small and medium enterprises (SMEs’) financial reporting practices in Austria. This report builds on the World Bank accounting and auditing reports on standards and codes (ROSC) methodology to give an overview of the Austrian corporate financial reporting system. It selectively provides good practice examples that can give incentives to overcome impediments to financial reporting reform. Based on the findings of two surveys conducted among Austrian SMEs and Austrian financial institutions, the report focuses particularly on aspects relevant to SME financial reporting. This report forms part of the activities of the center for financial reporting reform (CFRR) within the road to Europe program of accounting reform and institutional strengthening (REPARIS), which also provided funding.